Revisiting Two Robust Techniques for Contaminant Removal from Road Runoff - Budai, Péter (Periodica Polytechnica Civil Engineering, 2019)
Treatment of road runoff is a requisite for any environmentally sound infrastructure design. However, investment and maintenance budget is often a limiting factor during the planning and the operation phase of such projects. In order to cost-efficiently decrease the loads of a wide range of contaminants that are usually present in road runoff (posing a long-term threat to the aquatic and soil environments), simple and robust techniques are sought for. The paper deals with the re-evaluation of two such processes, sedimentation and filtration, putting emphasis on using authentic runoff samples during the tests in order to properly characterize the performance of these easy-to-manage solutions in this specific field of application. The results presented in this paper are aimed to aid the proper design of low-cost, low-maintenance road runoff treatment facilities, serving with background information that can be used to ensure that the expectations for the degree of pollutant removal are surely met.